The Role of Ethical Leadership on Employee Performance in Guilan University of Medical Sciences. (12th September 2016) - Kelidbari, Hamid Reza Rezaei; Fadaei, Mehdi; Ebrahimi, Pejman
Abstract: The aim of this research is to investigate the role of ethical leadership on employee's performance in Rasht University of Medical Sciences. The research method in this study is descriptive - correlation and based on the objective, it is an applied research. The statistical population of this research consisted of all employees of the University of Medical Sciences in the city of Rasht, which the number of sample size was determined 337 employees by the available non-probability sampling method. In order to collect data standard questionnaire was used, and finally 349 questionnaires were analyzed. In the inferential statistics, the Kolmogorov-Smirnov test was used to investigate the normality of data distribution. With regard to the normality of data distribution, in order to investigate the hypotheses, the parametric tests of Pearson correlation and hierarchical regression in SPSS software were used. In order to test the fitness of research model and investigating all relationships, the structural equation modeling in LISREL software was used. The research results showed that the role of ethical leadership in the performance of employees is indirectly significant and all hypotheses were confirmed.